Characterization of a Cu‐La0.75Sr0.25Cr0.5Mn0.5O3 ‐CeO2/La0.75Sr0.25Cr0.5Mn0.5O3‐YSZ/Ni‐ScSZ Three‐Layer Structure Anode in Thin Film Solid Oxide Fuel Cell Running on Methane Fuel1. Issue 2 (27th February 2015) - Huang, B.; Gu, X.‐Z.; Hu, Y.‐X.; Liu, Y.‐B.; Zhou, W.‐T.; Hou, C.‐Y.; Zhu, X.‐J.
Abstract Anodes for Solid Oxide Fuel Cell that is capable of directly using hydrocarbon without external reforming have been of great interest recently. In this paper, a three‐layer structure anode running on methane is fabricated by tape casting and screen printing method. The slurry of catalyst layer Cu‐LSCM‐CeO2 (with weight ratios of 1.5:7.0:1.5, 2.0:7.0:1.0, 2.15:7.0:0.85 and 2.25:7.0:0.75, weight ratios of Cu/CeO2 is 1:1, 2:1, 2.5:1 and 3:1, respectively) is screen‐printed on LSCM‐YSZ support layer and Ni‐ScSZ active layer. Thus, LSCM‐YSZ/Ni‐ScSZ anodes with Cu‐LSCM‐CeO2 catalyst layer (denoted as LSCM‐YSZ1010, LSCM‐YSZ2010, LSCM‐YSZ2510 and LSCM‐YSZ3010, respectively) are obtained. Single cells with three‐layer structure anode are also fabricated and measured, of which the maximum power density reaches 491 and 670 mW cm−2 for the cell with LSCM‐YSZ2510 anode running on methane at 750 °C and 800 °C, respectively. No significant degradation in performance has been observed after 240h of cell testing when LSCM‐YSZ2510 anode is exposed to methane at 750 °C. Very little carbon deposition is detected on the anode, suggesting that carbon deposition is limited during cell operation. Consequently, Cu‐LSCM‐CeO2 catalyst layer on the surface of LSCM‐YSZ support layer makes it possible to have good stability for long‐term operation in methane due to very little carbon deposition.